Impact of Hospital Delivery on Child Mortality: An Analysis of Adolescent Mothers in Bangladesh - Sarmistha Pal (Institute for the Study of Labor (IZA), 2015)
The present paper provides new evidence that hospital delivery can significantly lower child mortality risks, especially among vulnerable young adolescent mothers in Bangladesh. We exploit the exogenous variation in community's access to local health facilities (both traditional and modern) before and after the completion of the 'Women's Health Project' in 2005 (that enhanced emergency obstetric care in women friendly environment) to identify the causal effect of hospital delivery on various mortality rates among children born during 2002-2007. Our best estimates come from the parents fixed effects models that help limiting any parents-level omitted variable estimation bias. Ceteris paribus, access to family welfare clinic boosts hospital delivery likelihood, which in turn tends to lower neo-natal, early and infant mortality rates, especially among adolescent mothers after the completion of Women's Health Project.
Keywords: D13; I12; O15; 330; Women's Health Project; emergency and obstetric care; adolescent mothers; household fixed effects models; endogeneity and identification; access to health facilities; infant and child mortality indices